Stage as Street: Representation at the Juncture of the Arts and Justice - Dattatreyan, E. Gabriel (2013)
Arts educators working with court-involved youth face a set of complex and imbricated challenges. First, how do we gain the interest of the young people we would have participate in what we imagine are col-laborative and mutually generative projects? Second, how do we mediate representational tensions when the project is not solely therapeutic but has a broader public pedagogical purpose—to disrupt the simplistic and pathologizing discourses of poverty and violence that so often capture young men and women of color in the United States? (Bourgois, 2002; Noguera, 2008). Third, and not least, how do we navigate the institutional settings where our arts programs are situated, given that the institutions might have overlapping and divergent interests in promoting the arts and arts education